2020
DOI: 10.36680/j.itcon.2020.024
|View full text |Cite
|
Sign up to set email alerts
|

Construction 4.0: a survey of research trends

Abstract: The fourth industrial revolution, called Industry 4.0, is transforming decision-making through the increasing use of information and digitization technologies. While Industry 4.0 is expanding rapidly in manufacturing industries, its induced transformations are gradually affecting other sectors, including the construction industry. In recent years, the use of 4.0 technologies in the construction industry, termed as ‘Construction 4.0’, has increased, mostly due to the immense potential of Industry 4.0 for improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 71 publications
1
65
0
Order By: Relevance
“…Although the adoption costs of MR techniques are higher ultimately, the firms who will adopt this change will go out to win in the end. Overall, on a rudimentary level, MR will be embraced by the firms in the future at a vast level, as the onset of Construction 4.0 [23,71] will digitalize the industry, providing a paradigm shift in the working culture of AEC firms. The summary of definitions and applications of ImT's is presented in Table 3.…”
Section: Bim With Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the adoption costs of MR techniques are higher ultimately, the firms who will adopt this change will go out to win in the end. Overall, on a rudimentary level, MR will be embraced by the firms in the future at a vast level, as the onset of Construction 4.0 [23,71] will digitalize the industry, providing a paradigm shift in the working culture of AEC firms. The summary of definitions and applications of ImT's is presented in Table 3.…”
Section: Bim With Mrmentioning
confidence: 99%
“…Talking about the civil engineering aspects, Protchenko et al [21] used VR/AR solution to enhance the usefulness of the structural system, and Orihuela et al [22] proposed the application of the Lean philosophy with the use of immersive applications during the life cycle of a project at different steps. Many universities have increased their research programs focused on ImTs applications in recent years to explore the enormous amount of prominent ways to automate the AEC industry, especially after the outset of Industrial Revolution 4.0 (IR 4.0) [23]. From conceptual and theoretical frameworks to lab evaluated prototypes to field-based knowledge applied results, ImTs has transformed the nature of work in the AEC industry [24] and will continue to do so in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The research was conducted using a bibliometric analysis and by analyzing the keyword occurrence [50]. In the same year, Maskuriy et al [64] researched the application of 4IR technologies in construction and found that most integrated technologies have focused on the preconstruction phase. Furthermore, in the literature review in [65], it was noted that Germany leads the field of Construction 4.0, and is followed by China, the United States, etc.…”
Section: The Fourth Industrial Revolution (4ir)mentioning
confidence: 99%
“…The usage of BIM extends to more areas in the construction industry, e.g., transportation infrastructure (Costin et al, 2018). Perrier et al (2020) conclude that the information model is changing more and more into an integrated model (e.g., BIM combined with other technologies). Hence, Construction 4.0 technologies will continue to change all processes of construction project management (including time, personnel, communication, etc.).…”
Section: Introductionmentioning
confidence: 97%